2020
DOI: 10.1155/2020/8883046
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Enhances Episodic Memory in Healthy Older Adults by Modulating Retrieval-Specific Activation

Abstract: Memory decline has become an issue of major importance in the aging society. Anodal transcranial direct current stimulation (atDCS) is a viable tool to counteract age-associated episodic memory deterioration. However, the underlying neural mechanisms are unclear. In this single-blind, sham-controlled study, we combined atDCS and functional magnetic resonance imaging to assess the behavioral and neural consequences of multiple-session atDCS in older adults. Forty-nine healthy older adults received either 10 ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…A total of 991 participants participated in 9 RCTs [41‒45, 52‒55]. Fifteen task types were included: object-location learning, source memory task, item memory task, digit span forward task, Rivermead behavioral memory test, word memory task, auditory verbal learning test, wordlist learning task, logical memory, international shopping list test, one card-learning task, test de aprendizaje verbal España-Complutense, direct digits of the WAIS-III, and memory alteration test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 991 participants participated in 9 RCTs [41‒45, 52‒55]. Fifteen task types were included: object-location learning, source memory task, item memory task, digit span forward task, Rivermead behavioral memory test, word memory task, auditory verbal learning test, wordlist learning task, logical memory, international shopping list test, one card-learning task, test de aprendizaje verbal España-Complutense, direct digits of the WAIS-III, and memory alteration test.…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al [42] reported that the loss rate was 13.9%, so it was regarded as high risk. The remaining eight studies [41,[43][44][45][46][52][53][54][55] were considered low risk because the follow-up situation was clearly described or did not influence the meta-analysis result.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Neuroplasticity is based on cortical and neuronal excitability, and stimulating excitability with tDCS enhances cognitive processes [35], through the forti cation of neural connections [36,37] and, therefore, a recon guration of brain networks [38]. For example, Huo et al (2020) found that tDCS was effective when stimulating the DLPFC because neural changes in the prefrontal cortex resulted in better memory performance [39].…”
Section: Discussionmentioning
confidence: 99%
“…The results regarding the cognitive effects of tDCS in aging are mixed, as the administration of atDCS has not consistently resulted in the enhancement of cognitive functions in older individuals. Some tDCS studies have reported memory improvement in healthy older adults when stimulating the prefrontal cortex ( Manenti et al, 2013 , 2017 ; Sandrini et al, 2014 , 2016 , 2019 ; Medvedeva et al, 2019 ; Huo et al, 2020 ) or the left temporoparietal cortex ( Antonenko et al, 2019 ). On the other hand, other studies applying tDCS over the prefrontal cortex reported no effects or even a worsening in aging ( Leach et al, 2016 , 2019 ; Peter et al, 2019 ; Habich et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%